Evidence for the heterologous benefits of prior BCG vaccination on COVISHIELD™ vaccine-induced immune responses in SARS-CoV-2 seronegative young Indian adults - Rakshit, Srabanti; Adiga, Vasista; Ahmed, Asma; Parthiban, Chaitra; Chetan Kumar, Nirutha; Dwarkanath, Pratibha; Shivalingaiah, Sudarshan; Rao, Srishti; D’Souza, George; Dias, Mary; Maguire, Thomas J. A.; Doores, Katie J.; et al. (Frontiers in Immunology, 2022)
This proof-of-concept study tested if prior BCG revaccination can qualitatively and quantitively enhance antibody and T-cell responses induced by Oxford/AstraZeneca ChAdOx1nCoV-19 or COVISHIELDTM, an efficacious and the most widely distributed vaccine in India. We compared COVISHIELDTM induced longitudinal immune responses in 21 BCG re-vaccinees (BCG-RV) and 13 BCG-non-revaccinees (BCG-NRV), all of whom were BCG vaccinated at birth; latent tuberculosis negative and SARS-CoV-2 seronegative prior to COVISHIELDTM vaccination. Compared to BCG-NRV, BCG-RV displayed significantly higher and persistent spike-specific neutralising (n) Ab titers and polyfunctional CD4+ and CD8+ T-cells for eight months post COVISHIELDTM booster, including distinct CD4+IFN-+ and CD4+IFN-- effector memory (EM) subsets co-expressing IL-2, TNF- and activation induced markers (AIM) CD154/CD137 as well as CD8+IFN-+ EM,TEMRA (T cell EM expressing RA) subset combinations co-expressing TNF- and AIM CD137/CD69. Additionally, elevated nAb and T-cell responses to the Delta mutant in BCG-RV highlighted greater immune response breadth. Mechanistically, these BCG adjuvant effects were associated with elevated markers of trained immunity, including higher IL-1 and TNF-expression in CD14+HLA-DR+monocytes and changes in chromatin accessibility highlighting BCG-induced epigenetic changes. This study provides first in-depth analysis of both antibody and memory T-cell responses induced by COVISHIELDTM in SARS-CoV-2 seronegative young adults in India with strong evidence of a BCG-induced booster effect and therefore a rational basis to validate BCG, a low-cost and globally available vaccine, as an adjuvant to enhance heterologous adaptive immune responses to current and emerging COVID-19 vaccines.